Teaching Children & Young People with Special Educational Needs & Disabilities - Edited by Martin-Denham, Sarah (Los Angeles SAGE Publications Ltd., 2015)
A succinct, clear guide to working with pupils (birth to 25 years) with special educational needs and disabilities, providing suggested strategies and examples of lesson plans as well as detailed advice on sources of further information.
Include References and Index.
Covers all ages and relates to both special and mainstream settings. Written by a number of SEND experts it not only provides the theory but has great examples of good practice strategies you can use in the classroom"--Lorrain Petersen, back cover.
Keywords: People with disabilities--Education -- Special education